PELATIHAN JURNAL UMUM DAN BUKU BESAR PERUSAHAAN JASA - Henny Henny; Julio Cruise; Devilia Tanuwijaya; Belicia Rafaela Iskandar (Jurnal Bakti Masyarakat Indonesia, 2025)
Financial literacy is an essential competence that supports individuals in adapting to rapidly changing economic conditions. However, a considerable number of high school students still struggle to comprehend accounting practices conceptually and practically, particularly in recording financial transactions within service-based businesses. In response to this issue, a community service program was initiated by a team from Universitas Tarumanagara to strengthen students’ understanding of general journal preparation and the posting of balances to the general ledger. The program implemented a participatory education approach, supported by interactive group discussions that encouraged students to actively engage in case-based simulations and guided practice. Learning materials were presented through visual modules and structured exercises tailored to the literacy level of the participants, enabling them to construct knowledge through practical experience. To measure learning outcomes, pre-test and post-test assessments were administered as indicators of improvement in conceptual comprehension and procedural accuracy. The results revealed noticeable progress among most students, reflected in increased scores and improved precision in recording, classifying, and transferring account balances. In addition, students demonstrated a more positive attitude toward financial transparency and accuracy. Overall, this activity successfully enhanced practical accounting literacy among participants while serving as a concrete implementation of the Tri Dharma of Higher Education in the area of community service. The outcomes of this program highlight the importance of integrating interactive learning strategies to bridge the gap between theoretical instruction and real-world application, preparing students for academic progression as well as future employment challenges.   ABSTRAK Literasi keuangan merupakan kemampuan penting yang dibutuhkan individu untuk mampu beradaptasi dengan perkembangan ekonomi yang kompetitif. Namun demikian, masih banyak siswa sekolah menengah yang mengalami kesulitan dalam memahami proses akuntansi secara praktis, khususnya terkait pencatatan transaksi pada perusahaan jasa. Menyikapi kondisi tersebut, tim pengabdian kepada masyarakat dari Universitas Tarumanagara menyelenggarakan kegiatan pelatihan untuk meningkatkan pemahaman siswa mengenai penyusunan jurnal umum serta proses pemindahan saldo akun pada buku besar. Pelatihan ini menggunakan pendekatan pendidikan partisipatif yang dikombinasikan dengan diskusi kelompok interaktif, sehingga peserta dapat terlibat langsung melalui simulasi kasus dan latihan pencatatan. Materi pembelajaran disusun secara aplikatif melalui modul visual dan contoh transaksi yang disesuaikan dengan tingkat pemahaman peserta. Untuk melihat efektivitas pembelajaran, diberikan tes awal dan tes akhir sebagai indikator peningkatan pengetahuan konseptual dan kemampuan praktik penjurnalan. Hasil evaluasi menunjukkan bahwa sebagian besar peserta mengalami peningkatan ketelitian dalam mencatat transaksi, menggolongkan akun, serta memindahkan saldo ke buku besar secara sistematis. Selain itu, peserta juga menunjukkan sikap yang lebih positif terhadap penerapan transparansi dan akurasi keuangan. Secara keseluruhan, kegiatan ini berhasil memperkuat literasi keuangan praktis pada siswa serta menjadi bentuk nyata implementasi Tri Dharma Perguruan Tinggi dalam bidang pengabdian kepada masyarakat. Temuan ini menegaskan pentingnya penerapan metode pembelajaran interaktif untuk menjembatani kesenjangan antara teori dan praktik, mempersiapkan siswa untuk kemajuan akademis serta tantangan pekerjaan di masa depan.